A forma bela na Crítica da faculdade de julgar - Ana Carolina de Carvalho Belmani (2017)
In the present work, we will analyse the concept of beautiful form in the Critique of judgement, in view of its relation to the faculty of imagination and the reflexive aesthetic character of pure judgments of taste. Through the explanation of the specific activity of imagination in this judgment, we intend to make plain the aesthetic apprehension process and the production of beautiful form. In order to do so, we will present the importance of the principle of purposiveness without a purpose in Kant’s theory of taste, the differences between the beautiful and the sublime and the relation between aesthetical ideas and form. We will also discuss the implications of the capabilities and limits of imagination in its cognitive function from the Critique of pure reason in judgements of taste. With this, we intend to shed light to some seemingly ambiguous question concerning beautiful form, such as the subjective non-determinant way beauty refers to its object, the schematism without concepts and the imagination free-conformity to laws.